Food, Farms, and Solidarity : French Farmers Challenge Industrial Agriculture and Genetically Modified Crops - Heller, Chaia (Book collections on Project MUSE., 2013)
Chaia Heller follows one of France's largest farmers' unions as it joins with peasants internationally to contest the hegemony of genetically modified foods, free trade, and industrial agriculture.